Hidden miners – the roles of cover crops and soil microorganisms in phosphorus cycling through agroecosystems - Hallama, Moritz; Pekrun, Carola; Lambers, Hans; Kandeler, Ellen (Plant and soil, 2019)
Background Phosphorus (P) is a limiting nutrient in many agroecosystems and costly fertilizer inputs can cause negative environmental impacts. Cover crops constitute a promising management option for sustainable intensification of agriculture. However, their interactions with the soil microbial community, which is a key driver of P cycling, and their effects on the following crop, have not yet been systematically assessed. Scope We conducted a meta-analysis of published field studies on cover crops and P cycling, focusing on plant-microbe interactions. Conclusions We describe several distinct, simultaneous mechanisms of P benefits for the main crop. Decomposition dynamics, governed by P concentration, are critical for the transfer of P from cover crop residues to the main crop. Cover crops may enhance the soil microbial community by providing a legacy of increased mycorrhizal abundance, microbial biomass P, and phosphatase activity. Cover crops are generally most effective in systems low in available P, and may access ‘unavailable’ P pools. However, their effects on P availability are difficult to detect by standard soil P tests, except for increases after the use of Lupinus sp. Agricultural management (i.e. cover crop species selection, tillage, fertilization) can improve cover crop effects. In summary, cover cropping has the potential to tighten nutrient cycling in agricultural systems under different conditions, increasing crop P nutrition and yield.